Symphony No. 1 in D Major Titan - Mahler, Gustav. 1860-1911 (Colección Dover Miniature Scores, 1998)
A staple of the orchestral repertoire, this superb work is presented here in full score with bar-numbered movements. ideal for study in the classroom, at home or in the concert hall, this affordable, high-quality, conveniently sized volume will be edition of choice for music students and music lovers alike.